2010
DOI: 10.1021/jp106354d
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Applicability of Electron-Counting Rules in Transition Metal Encapsulating Ge Cage Clusters

Abstract: The relative stability of Sc, Ti, and V encapsulating Ge(n) clusters in the size range n = 14-20 has been studied through first-principles electronic structure calculations based on density functional theory. Variations of the embedding energy, gap between the highest occupied and the lowest occupied molecular orbitals, ionization potential, vertical detachment energy, and electron affinity with cluster size have been calculated to identify clusters with enhanced stability. The enhanced stability of some clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
60
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 30 publications
2
60
1
Order By: Relevance
“…Kumar and Kawazoe conducted theoretical calculations on a number of TM-doped germanium clusters and predicted TiGe 16 cluster to be a Frank-Kasper polyhedron structure with a large gap between its highest-occupied-orbital (HOMO) and lowest-unoccupied-orbital (LUMO) [9]. In addition to the TiGe 16 cluster, the density functional theory (DFT) calculations of Bandyopadhyay et al on TiGe n (n=14−20) suggested that TiGe 18 cluster also has en-hanced stability [10]. The ground state structure of TiGe 12 cluster is proposed to be a remarkably stable pseudoicosahedron by Tang et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…Kumar and Kawazoe conducted theoretical calculations on a number of TM-doped germanium clusters and predicted TiGe 16 cluster to be a Frank-Kasper polyhedron structure with a large gap between its highest-occupied-orbital (HOMO) and lowest-unoccupied-orbital (LUMO) [9]. In addition to the TiGe 16 cluster, the density functional theory (DFT) calculations of Bandyopadhyay et al on TiGe n (n=14−20) suggested that TiGe 18 cluster also has en-hanced stability [10]. The ground state structure of TiGe 12 cluster is proposed to be a remarkably stable pseudoicosahedron by Tang et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2,4,8–10 ] Density functional theory was also employed to study the stability and electronic structures of a large number of transitions metal‐doped germanium clusters. [ 1,4–29 ] It was found in many cases that doping transition metal atom can lead to stable transition metal‐doped germanium clusters. [ 1,2,6,7,19,21 ]…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical properties of transition metal‐doped germanium clusters are determined by their size, shape, and composition. In the literature, we can see a large amount of experimental and theoretical investigations on the structures of transition metal‐doped germanium clusters . It is found that doping of transition metal to pure germanium clusters can form stable cage structures that can be used as building blocks for synthesis novel materials …”
Section: Introductionmentioning
confidence: 99%